Strategi Layanan Anak Dalam Menumbuhkan Minat Baca Anak di Dinas Perpustakaan dan Arsip Kota Binjai - Elgy Wijayanti; Neila Susanti; Yusniah Yusniah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study discusses Children's Service Strategies in Fostering Children's Interest in Reading at the Binjai City Library and Archives Service. The goal to be achieved from this research is to find out how the child service strategy is in the Binjai City Library Service. This research method uses a qualitative descriptive approach. By using data collection techniques through interviews, observation and documentation. The informants in this study were librarians at the Library Service who the researchers had chosen according to the criteria for research subjects.The results showed that the child service strategy carried out by librarians at the Binjai City Library Service was carried out using several child service activities in the form of reading tours, reading corner services for toddlers in Binjai City, mobile library services specifically for children, reading terrace services in Binjai City, collaboration with PKK mothers. and Promotions. Where the promotion is carried out using brochures and social media, namely Instagram.